The primacy of the principle of preclusion in the intermediate stage to the detriment of the right of defense - Flores Rivera, Edilberto Freed (2023)
The purpose of this article is to identify how the primacy of the principle of preclusion in the intermediate stage influences the detriment of the right to defense, specifically in the stage of response to the accusatory requirement, where the procedural parties have ten days to present formal and substantial observations and offer evidence to be processed and evaluated in the oral trial. The problem lies in the fact that the accused, as a result of an ineffective defense, does not offer any evidence within the ten days, and the principle of preclusion will prevail, since the preparatory investigation judge will not admit any evidence outside the legal period; this will lead to a scenario of procedural defenselessness in the oral trial.